The Difficulty of English Student Studying TOEFL - Safitri, Lela; Andini, Novita; Maghfirah, Annisa; Rahmatika, Alvi (Indonesian Journal of ELT and Applied Linguistics, 2023)
The aim of this research is to determine the difficulties of english students in studying toefl. The approach used in this research is descriptive qualitative with students from the university of north sumatra by conducting interviews as a data collection tool. The research results show that there are several main factors that make it difficult for students to study toefl, namely lack of time management, lack of practice, lack of mastery of indonesian and english vocabulary and pronunciation. Tujuan dari penelitian ini adalah untuk mengetahui kesulitan siswa bahasa inggris dalam belajar toefl. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan mahasiswa Universitas Sumatera Utara dengan melakukan wawancara sebagai alat pengumpulan data. Hasil penelitian menunjukkan bahwa terdapat beberapa faktor utama yang menyebabkan siswa kesulitan dalam belajar toefl yaitu kurangnya manajemen waktu, kurangnya latihan, kurangnya penguasaan kosa kata dan pengucapan bahasa indonesia dan inggris.